The Return of Memory: Architecture and Landscape in Wienfried Georg Sebald’s Austerlitz and in the Autobiographical Stories of Lithuanian Exiles - Bernotienė, Gintarė (Colloquia, 2024)
In the 1930s and 1940s, the mass destruction of ethnoses and deportations of populations, which shattered the fates of states and people, shock Eastern Europe. In contemporary theories of trauma and memory studies, in addition to the political evaluation of those events, the study of place-based memory has been gaining attention, turning the research of cultural and individual memory back to the fundamental conflict provoked by the loss of place—the erosion of the connection with the land (place), which forms the base of person’s identity. In this article, I analyze the narratives of different national experiences—Sebald’s novel Austerlitz and the egodocumentary of Lithuanian exiles—from the perspective of place, tracing the impact of landscape and architecture on the memory processes of genocide survivors, as expressed in the specific literary works and testimonies. By reasoning that the criteria of the historicity and documentary character and the qualities of the narratives as transmitting traumatic experiences validate the comparison of the novel and testimonies, I ask why the compositional role of the reflection of the place, i.e., landscape and architecture, in organizing the novel’s narrative has been missing in the autobiographical texts of exiles, who have experienced similar complications of their displacement and identity. Different assessments of the existential situation (the novel emphases the hopelessness and abnormality of the genocide, whereas the memoirs of the exiles focus on the effort to make the situation as normal as possible), which I treat as identifiers of the meaningfulness of the experiences, do not obscure the similarities in the narratives, that is, the subjects’ complicated relationship to and the symbolic meaning-making of the place, and the search for alternative topoi, which are evident throughout the stories. The metaphor of the abyss, used in Sebald’s novel to manifest the irretrievability of the past, can be recognized in the descriptions of the social abyss that appear in the memories of the exiles.